Longitudinal association of midlife vision impairment and depressive symptoms: the study of Women's Health Across the Nation, Michigan site. Issue 1 (January 2022) - Karvonen-Gutierrez, Carrie A.; Kumar, Navasuja; Hood, Michelle M.; Musch, David C.; Harlow, Sioban; Moroi, Sayoko E.
Abstract: Objective: Poor vision affects physical health but the relationship with depressive symptoms among midlife adults (40-65 y), who often present with early stage vision impairment (VI), is not well understood. The goal of this study was to assess the impact of vision on depressive symptoms during midlife. Methods: The Michigan site of the Study of Women's Health Across the Nation conducted assessments of distance visual acuity at six consecutive, near-annual follow-up visits. At each visit, depressive symptoms (Center for Epidemiological Studies-Depression Scale) were assessed. VI was defined as mild (20/30-20/60) or moderate-severe (20/70 or worse). Multivariable logistic regression models using generalized estimating equations were used to assess the association of VI and reporting of depressive symptoms at the subsequent visit. Results: At analytic baseline, the mean age of participants ( N = 226) was 50.0 years (standard deviation = 2.6). More than half (53.5%) of women had mild VI and 8.0% had moderate-severe VI. Adjusting for age, preexisting depressive symptoms, race, education, economic strain, body mass index, and smoking, participants with mild and moderate-severe VI had 68% (95% C (0.97-2.90)) and 2.55-fold (95% CI 1.13-5.75) higher odds of reporting depressive symptoms at their subsequent study visit as compared with women without VI. Further adjustment for diabetes, hypertension, and osteoarthritis attenuated the estimates and the associations were no longer statistically significant. Conclusion: VI was associated with increased odds of future depressive symptoms among mid-life women. Timely detection and appropriate correction of VI may be important to consider in maintaining the mental health status of midlife women. Abstract : Supplemental Digital Content is available in the text